Minimally Invasive Excision of a Giant Paratubal Cyst: Case Report and Management Review - Bassem Skaff; Dani Zoorob; Rawane El Assaad; Mohamad Abou-Baker (Case Reports in Obstetrics and Gynecology)
Paratubal cysts are usually incidentally found due to being small and asymptomatic adnexal structures. Enlargement to more than 15 cm concurrent with late presentation in an adult is rare. We present the case of a 36 cm diameter cyst in a 31-year-old female whose symptoms involved overactive bladder, abdominal bloating, and pressure. Radiologic findings suggested that it extended from the xiphoid and pubic symphysis. Removal was through a minimally invasive technique.